1828 Fla. Acts 24, An Act To Prevent Fire Hunting - (:unkn) unknown (General Publisher, 1828)
Prohibited hunting by fire light in the night time with a gun or other firearms and not on one's own private property. Violators fined not exceeding twenty-five dollars, or imprisoned not exceeding one month at discretion of the court.
--
Keywords: HUNTING REGULATION